Ichnoentomology : insect traces in soils and paleosols - Genise, Jorge Fernando (Topics in geobiology., 2016)
This book is devoted to the ichnology of insects, and associated trace fossils, in soils and paleosols. The traces described here, mostly nests and pupation chambers, include one of the most complex architectures produced by animals. Chapters explore the walls, shapes and fillings of trace fossils followed by their classifications and ichnotaxonomy. Detailed descriptions and interpretations for different groups of insects like bees, ants, termites, dung beetles and wasps are also provided. Chapters also highlight the the paleoenvironmental significance of insect trace fossils in paleosols for paleontological reconstructions, sedimentological interpretation, and ichnofabrics analysis. Readers will discover how insect trace fossils act as physical evidence for reconstructing the evolution of behavior, phylogenies, past geographical distributions, and to know how insects achieved some of the more complex architectures. The book will appeal to researchers and graduate students in ichnology, sedimentology, paleopedology, and entomology and readers interested in insect architecture.- Resumé vydavatel